2020
DOI: 10.1016/j.ygeno.2020.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of ARL9 and its methylation in low-grade glioma

Abstract: This study aimed to determine the value of ARL9 expression or methylation as a biomarker for LGG survival. We investigated the expression, methylation, prognosis and immune significance of ARL9 through bioinformatics analysis. ARL9 is negatively regulated by ARL9 methylation, leading to its low expression in LGG tissues. Both low ARL9 expression and hypermethylation predicted favorable OS and PFS in LGG patients, according to the TCGA database. Cox regression demonstrated that low ARL9 expression and ARL9 hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Almost all sites were signi cantly related to OS, which veri ed the prognostic relevance of EMILIN2. Many studies have indicated that the relationship between speci c DNA methylation sites and the expression of neighbouring genes ranges from weak to moderate, and there are few genes that are regulated by DNA methylation [1,[5][6][7]. In our study, we found that EMILIN2 was obviously and negatively regulated by its DNA methylation.…”
Section: Discussion/conclusionsupporting
confidence: 51%
See 1 more Smart Citation
“…Almost all sites were signi cantly related to OS, which veri ed the prognostic relevance of EMILIN2. Many studies have indicated that the relationship between speci c DNA methylation sites and the expression of neighbouring genes ranges from weak to moderate, and there are few genes that are regulated by DNA methylation [1,[5][6][7]. In our study, we found that EMILIN2 was obviously and negatively regulated by its DNA methylation.…”
Section: Discussion/conclusionsupporting
confidence: 51%
“…Low-grade glioma (LGG) is a common primary malignant brain tumour that has great intrinsic heterogeneity in tumour biological behaviour [1]. Grade II and III gliomas, which have a median survival of more than 7 years, are collectively termed diffuse lower-grade gliomas [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated the differences between the high- and low-risk groups in the abundance of 22 immune cells and the expression levels of immune-related molecules. Besides, we applied Pearson correlation analysis to calculate the correlation between risk scores and the expression levels of immune cell markers, which were well elucidated by previous studies ( Danaher et al, 2017 ; Tan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…HIST1H2BK was identified as an indicator of poor prognosis and a promising biomarker for the treatment of low-grade glioma (LGG) ( Liu et al, 2020 ). Similarly, ARL9 had been shown its prognostic value in LGG, and probably played an important role in immune cell infiltration ( Tan et al, 2020 ). All these markers are possible used for advanced decision-making processes in the future; however, many more potential prognostic indicators still need to be explored in gliomas.…”
Section: Introductionmentioning
confidence: 96%